Identifikasi Diskontinuitas Seismik Mantel di Barat Laut Pulau Sumatera Menggunakan Data Prekursor SS - Fahruddin Fahruddin; Apriadi Apriadi; Ibrahim Sota; Sadang Husain (Jurnal Fisika FLUX, 2020)
410km and 660km discontinuities are very clear and very easily identified discontinuities other than the Moho layer. This research utilizes SS precursor data, bouncepoints in the northern part of Sumatra. The data used is the depth of the epicenter <70 km, earthquake magnitude 5.5 and the distance between the epicenter and earthquake recording station more than 1000. This study is a preliminary study to determine changes in the depth of discontinuity in the study area. The SS phase is very well observed in the transversal component seismogram which is the result of the rotation of two horizontal components NS and EW, to obtain a good seismogram a 0.03Hz low pass filter is performed. In this study used 38 data transversal component seismograms, from 76 horizontal component seismograms. The most important thing in this study is the determination of the SS phase used as a reference (point 0), the SS phase is determined using the AK135 table guide, then the SS precursors are determined which can be seen at 450 seconds, 300 seconds, 90 seconds and 50 seconds before the SS . SS prekursors that are very clear at 450 seconds, are strongly suspected as a 660 km discontinuity. SS prekursors can be seen clearly after the stacking process.